2022
DOI: 10.4103/ccd.ccd_154_20
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Ridge Augmentation Using Autogenous Bone Graft and Platelet-Rich Fibrin to Facilitate Implant Placement

Abstract: The maxillary anterior region is considered to be the esthetic zone of human dentition. Missing teeth in this area leads to severely compromised esthetics and function. Endosseous implants are a viable treatment option in this scenario, but the placement of endosteal implants requires adequate bone volume for successful osseointegration. When the morphology of the bone does not allow proper implant placement, there are various bone augmentation procedures which aid in reconstruction of the residual alveolar ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Meanwhile, the study with the Chelsea scale with 2D assessment of resorption rate showed no significant differences between the two groups at 6 months. At 6 months post surgery, the early remodelling phase of the bone is seen where the grafted bone then undergoes a lot of physiological remodelling of the bone grafting [14,22,23]. Although 2D radiographs are still routinely used along with the clinical outcome for bone grafting, the images from these radiographs are unable to provide the volume, morphology, or architecture of the regenerated bone in the cleft defect area [14].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the study with the Chelsea scale with 2D assessment of resorption rate showed no significant differences between the two groups at 6 months. At 6 months post surgery, the early remodelling phase of the bone is seen where the grafted bone then undergoes a lot of physiological remodelling of the bone grafting [14,22,23]. Although 2D radiographs are still routinely used along with the clinical outcome for bone grafting, the images from these radiographs are unable to provide the volume, morphology, or architecture of the regenerated bone in the cleft defect area [14].…”
Section: Discussionmentioning
confidence: 99%
“…Другой нерешенной проблемой трансплантологии остается увеличение размера альвеолярного гребня при значительном уменьшении его размера, так как без этого осложняется внедрение имплантата в выбранном месте [ 8 ] . Указанная проблема остается нерешенной, несмотря на то что существует множество процедур аутогенной костной пластики, таких как дистракционный остеогенез, направленная регенерация кости, аутогенная пластика накладными блоками, установка вкладок, «тент-штанга» и вертикальная реконструкция с использованием титановой сетки для увеличения доступной высоты кости при внедрении имплантата [ 9,10 ] .…”
Section: For Citationunclassified
“…In a case study, block bone autografts taken from the mandibular symphysis were successfully used for localized alveolar ridge augmentation before implant placement. Autogenous bone grafts from the mandibular symphysis can be used for alveolar ridge augmentation [40]. The success rate of guided bone regeneration and autogenous bone grafts for lateral ridge augmentation is high.…”
Section: Autogenous Bone Graft For Ridge Augmentationmentioning
confidence: 99%